Kajian Hukum Terhadap Anak Berhadapan Hukum Dalam Tindak Pidana Pencurian Menurut Undang-Undang No. 11 Tahun 2012 Tentang Pengadilan Anak - M Syahputra Lubis; Sri Hidayani; Muazzul Muazzul (Universitas Medan Area, 2021)
Children are an inseparable part of human survival and the survival of the nation and state. In the Indonesian constitution, children have a strategic role that is expressly stated that the state guarantees the right of every child to survival, growth and development as well as protection from violence and discrimination. Therefore, the best interests of children should be lived out as the best interests for the survival of humanity. The legal consequences of criminal acts of theft committed by children are reviewed in accordance with Law No. 11 of 2012 and based on decision No. 67 / Pid.Sus-Anak / 2017 / PN.Mdn is imprisonment for two years because child offenders are proven to have committed theft by violence. Consideration of the judge on Decision No. 67 / Pid.Sus-Anak / 2017 / PN.Mdn in terms of imposing punishments on the perpetrators of criminal acts of theft committed by children is that the acts committed have fulfilled the elements in the indictment, namely Article 365 paragraph 1 to 1e and the second Criminal Code, and consider incriminating matters, namely the actions of the perpetrators disturbing the community and harming the victim and considering mitigating matters, namely the defendant is polite and has never been punished.